Guatemala - Croy, Anita (Washington, D.C. : National Geographic, 2009)
Although Guatemala is recovering from the wounds of military dictatorships and guerilla warfare, it possesses a gritty determination to keep the glorious colors of Mayan culture flying. Its volcanoes can seem the highest and most active, its Mayan ruins the most ruinous, its colonial cities the most historic, its jungles the most impenetrable, its coral reefs the most beautiful, and its flora and fauna some of the most unusual in the world.
Geography -- Nature -- History -- People & culture -- Government & economy.
OSLIS\Gale Nat Geo eBooks(2/2/23).
Includes bibliographical references (p. 61) and index.
Description based on print version record.
Keywords: Guatemala -- Juvenile literature; Guatemala; Electronic books- OSLIS; Electronic books